Makna hidup dalam hubungan antara penggunaan media sosial dan alienasi akademik pada mahasiswa - Ramadhani, Safira Dhia; Habibi, Ahmad Iqbal; Nufaisah, Alya (Maliki Interdisciplinary Journal, 2025)
Social media is a digital platform that facilitates information exploration and communication between people. However, previous studies have found both negative and positive correlations with students’ academic quality. This study examines in depth how social media affects the psychological well-being of students’ academics. It aims to analyze the negative and positive impacts with a focus on alienation and suitable strategies to use. Through literature analysis and empirical studies, the review results show that there is a correlation between the intensity of social media use and student academic alienation, where social media influences social comparison and its level of use correlates with the level of academic stress, which ultimately leads to alienation. This article offers an alternative perspective for understanding the impact of social media on student well-being and provides valuable insights for policymakers, educators, and mental health practitioners in designing programs and services that are responsive to student needs so that students can thrive and reach their maximum potential in the digital age.